Predicting neuropathy and reactions in leprosy at diagnosis and before incident events-results from the INFIR cohort study. - W Cairns S Smith; Peter G Nicholls; Loretta Das; Pramila Barkataki; Sujai Suneetha; Lavanya Suneetha; Rupendra Jadhav; P S S Sundar Rao; Einar P Wilder-Smith; Diana N J Lockwood; Wim H van Brakel (PLoS Neglected Tropical Diseases, 2009)
BACKGROUND: Leprosy is a disease of skin and peripheral nerves. The process of nerve injury occurs gradually through the course of the disease as well as acutely in association with reactions. The INFIR (ILEP Nerve Function Impairment and Reactions) Cohort was established to identify clinically relevant neurological and immunological predictors for nerve injury and reactions. METHODOLOGY/PRINCIPAL FINDINGS: The study, in two centres in India, recruited 188 new, previously untreated patients with multi-bacillary leprosy who had no recent nerve damage. These patients underwent a series of novel blood tests and nerve function testing including motor and sensory nerve conduction, warm and cold detection thresholds, vibrometry, dynamometry, monofilament sensory testing and voluntary muscle testing at diagnosis and at monthly follow up for the first year and every second month for the second year. During the 2 year follow up a total of 74 incident events were detected. Sub-clinical changes to nerve function at diagnosis and during follow-up predicted these new nerve events. Serological assays at baseline and immediately before an event were not predictive; however, change in TNF alpha before an event was a statistically significant predictor of that event. CONCLUSIONS/SIGNIFICANCE: These findings increase our understanding of the processes of nerve damage in leprosy showing that nerve function impairment is more widespread than previously appreciated. Any nerve involvement, including sub-clinical changes, is predictive of further nerve function impairment. These new factors could be used to identify patients at high risk of developing impairment and disability.